Analysis Of The Effectiveness Of Accounting Information Systems Over Accounts Receivable Control At PT Indoarsip Medan - Fiddarain, Khairah; Syafina, Laylan; Nastion, Yenni Samri Juliati (UNIVERSITAS PAKUAN, 2024)
This The importance of accounting information systems in improving maximum control of receivables. Better results are achieved with the effective use of information systems as a tool for making decisions. The aim of this research is to analyze the level of effectiveness of the accounting information system for controlling receivables at PT Putraduta Buanasentosa Indoarsip Medan by analyzing using the method of measuring the level of effectiveness with the Dean J. Champion formula. Several aspects used in measuring effectiveness are indicators of accounting information systems according to DeLone and McLean, components of accounting information systems, and control of receivables according to (COSO). The research results show that the accounting information system indicators are less effective with a result of 42%, the accounting information system components are quite effective with a result of 56%, and control of receivables is less effective with a value of 50%. This shows that the accounting information system for controlling receivables at PT Putraduta Buanasentosa Indoarsip Medan needs to improve the quality of the system in providing services to customers, and there needs to be a separation of duties and good control management so that the company's targets can be achieved.